EKSPLORASI ETNOMATEMATIKA PERAHU SANDEQ SEBAGAI KONTEKS PEMBELAJARAN PERBANDINGAN DAN SKALA UNTUK MENINGKATKAN KEMAMPUAN LITERASI NUMERASI SISWA TINGKAT SMP - Afdhal; Salsa; Milha Indriana; Nurul Azizah; Dahlia; Andi Heriani (Berajah Journal, 2026)
This study aims to explore the concept of ethnomathematics in the Sandeq boat and to examine the effectiveness of its application in learning ratios and scale to improve numeracy literacy of junior high school students. This study uses an ethnomathematics approach with a design that integrates qualitative exploration of cultural elements and their implementation in classroom learning. The research subjects are grade IX students. Data were collected through observation, interviews, and documentation. The results of the study show that the Sandeq boat contains mathematical concepts, especially ratios and scale, which can be identified through the size, shape, and proportion of the parts of the boat. The implementation of ethnomathematics-based learning shows an increase in students' numeracy literacy, which is indicated by the ability to understand contextual problems, formulate mathematical models, solve problems systematically, and interpret results. In addition, students show positive responses and more active engagement during the learning process. Thus, ethnomathematics-based learning on the Sandeq boat is effective in improving students' numeracy literacy on ratio and scale material.